Avaliação do potencial do bagaço de laranja industrial peletizado para a produção de butanol por Clostridium beijerinckii via fermentação acetona-butanol-etanol - Silva, Gabriela Fiori (Universidade Federal de São Carlos, 2019)
Among the lignocellulosic biomass produced in large quantities in Brazil, the production of orange juice stands out. This residue can be considered as source of raw material in fermentative processes and consequently leading to a generation of value-added products. Acetone-butanol-ethanol fermentation (ABE) may be a fermentation process of anaerobic bacteria sources of carbon from agro-industrial waste. Thus, the present study had to evaluate the butanol via ABE fermentation using Clostridium beijerinckii from pelletized industrial orange pomace. This bagasse was milled, chemically compounded and quantified as to its composition in holocellulose (18.99 %), alfacelulose (5.37 %), hemicellulose (13.62 %), lignin (6.16 %), pectin (7.21 %) and protein (3.14 %) and is subjected to a pretreatment of ultrasound, autohydrolysis and acid-diluted followed by enzymatic hydrolysis to verify an amount of fermentable total reducing sugars (ART). The ABE fermentation was carried out in batch-reactors at 37 °C under agitation of 160 rpm under anaerobic conditions. During a fermentation samples were taken for analyzes of sugars and solvents. Pretreatments followed by enzymatic hydrolysis do not enhance a significant amount of available ART compared to bagasse rather than enzymatic hydrolysis. At the end of the enzymatic hydrolysis, it was possible to obtain 4,301 g/L of sugars in the liquid phase (hydrolyzed) and can be fermented. At the end (120 h) of the orange hydrolysate fermentation the consumption of sugars was 75.42%, and at 78.10% for the control using glucose, butanol production was 0.069 g/L (yield 0.02 g/g) and 0.237 g/L (yield 0.071 g/g), respectively. Production of solvent has shown that orange pomace has potential for ABE fermentation.
Assessment of industrial orange pomace pelletized for butanol production by Clostridium beijerinckii by acetone-butanol-ethanol fermentation
Keywords: Pré-tratamento; Biomassa; Fermentação ABE; Pretreatment; Biomass; ABE fermentation; CIENCIAS BIOLOGICAS::MICROBIOLOGIA